Gender and HIV/AIDS in Bangladesh: A review - Joydeb Garai (Journal of Health and Social Sciences)
Introduction: The HIV/AIDS epidemic portrays a growing health threat in the world. In Bangladesh, the prevalence rate of HIV/AIDS is not yet high but it is gradually becoming a threat especially for women and young girls due to gender disparity. This systematic review was conducted to explore the gender-specific vulnerability to HIV/AIDS in Bangladesh in order to suggest to policy makers the best way for the prevention of HIV/AIDS in Bangladesh as well as in other low income countries. Methods: Peer review articles were identified using a systematic search of two databases: Pubmed and Goggle Scholar. The search was limited to studies published in English between 1998 and 2016 and included a special focus on articles addressing the gender-specific risk factors to HIV/ AIDS. Discussion and Conclusion: This paper analyzes how women and girls in marginalized position in the society fall victim to HIV/AIDS due to gender disparities and other related issues. The findings of the study indicate that women and young girls are the most vulnerable to HIV/AIDS infection among the general people. Along with biological susceptibility, other major causes of this vulnerability of women and girls are gender inequality, sexual abuse and violence, social stigma, inability to decision making power, economic dependency and men’s sexual power and privilege over women. This paper helps policy makers and invites them to take special care to reduce gender inequality before implementing any policy for the prevention of HIV/AIDS in Bangladesh as well as in low income countries.